Preserving stability and promoting growth - World Bank (Springer, 2015)
Developing countries in the East Asia Pacific region will see stable economic growth this year, bolstered by a recovery in high-income economies and the market's modest response so far to the Federal Reserve's tapering of its quantitative easing. Developing East Asia will grow by 7.1 percent this year, largely unchanged from 2013, the report says. As a result, East Asia remains the fastest growing region in the world, despite a slowdown from the average growth rate of 8.0 percent from 2009 to 2013. In China, growth will ease slightly, to 7.6 percent this year from 7.7 percent in 2013. Excluding China, the developing countries in the region will grow by 5.0 percent, slightly down from 5.2 percent last year.